PENGARUH SKALA OPERASI DAN STRUKTUR MODAL TERHADAP KINERJA OPERASI BANK UMUM-BPR - Sri Nugroho, Arif Julianto (Benefit: Jurnal Manajemen dan Bisnis, 2006)
This study describes the effect of asset structures and capital structures on bank financialperformance. Recently, bank financial performance could be seen through bankâs financial reportpublished on mass media. The measurement criterias of bank performance are established by BankIndonesia based on five aspects of CAMEL ie capital adequacy ratio, assets quality, management,earnings power and liquidity. This research involves 15 Public Banks and 15 BPRâs at Klaten as samples. The sample periodsin this research is one year 2005. The result shows that the capital adequacy ratio, assets quality,rentability or earnings power, liquidity are not influenced by assets structures and capital structures